A book of Narnians : the Lion, the Witch, and the others - Riordan, James, 1936-2012.; Baynes, Pauline; Lewis, C. S. (Clive Staples), 1898-1963. (New York, NY : HarperCollins, 1995)
Introduces, in text and illustrations, the various characters that inhabit the world of Narnia and sets them in the context of the Narnia stories. Also includes an outline of Narnian history.
Keywords: Lewis, C. S. -- 1898-1963. -- Juvenile literature; Lewis, C. S. -- 1898-1963 -- Characters -- Juvenile literature; Lewis, C. S. -- 1898-1963.; Children's stories, English -- History and criticism -- Juvenile literature; Fantasy fiction, English -- History and criticism -- Juvenile literature; Christian fiction, English -- History and criticism -- Juvenile literature; Children -- Books and reading -- Great Britain -- History -- 20th century -- Juvenile literature; Narnia (Imaginary place) -- Juvenile literature; Characters in literature